EFFICACY OF VARIOUS METHODS FOR DIAGNOSIS OF PYOMETRA IN BITCHES - Jena, Basanti; Rao, K Sadasiva; Das, D; Reddy, KCS (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The aim of the study was to evaluate efficacy of various methods of diagnosis of pyometra in bitches. All the bitches suspected for pyometra (n=28) were subjected to diagnostic methods like abdominal palpation, radiography, ultrasonography and haematological examination. Abdominal palpation revealed an obvious uterine enlargement. Lateral abdominal radiograph of bitches revealed a fluid filled dense tubular structure larger in diameter than small intestinal loops in ventral and caudal area of abdomen displacing loops of intestine dorsally and cranially. Ultrasonography of bitches with pyometra revealed an enlarged uterus with convoluted, tubular horns filled with anechoic to hypoechoic fluid. Leucocytosis with absolute neutrophilia was the most common finding in the pyometra affected bitches. Among the different methods of diagnosis of pyometra, ultrasonography was found to be the most efficient method.